VISUAL PRESERVATION OF JARAN KEPANG IN TEMANGGUNG THROUGH ESSAY PHOTOGRAPHY - Aziz, Abdul; Felix, John; Sonia, Candy Reggi (Capture : Jurnal Seni Media Rekam, 2018)
Performance art of ‘braid horse’ (jaran kepang) Temanggung is one of the original traditional arts that developed on the island of Java, especially Temanggung Regency. The researcher tried to lift the Temanggung ‘braid horse’ as an object of artistic research with the theme of preservation of the visual arts. This is an effort to preserve the Temanggung ‘braid horse’ through visual media, namely photography. The researcher documented that art with photo media. The purpose of this artistic research is to make photography work as an effort topreserve the ‘braid horse’ art culture with a journalistic documentation genre in the form of essay photography. The research model used in this study is to use the Visual Methodology and also with Roland Barthes's Semiotic analysis, where the power of photography is the power of the visual language that will speak. The results of this study are an essay photography book as an effort to preserve ‘braid horse’ in the genre of journalistic documentation.